Answer:
[tex](y-3)^2=-4(x+5)[/tex]
Step-by-step explanation:
Given the directrix is vertical, the parabola must have a horizontal axis since it's perpendicular to the directrix.
Therefore, we can use the form [tex](y-k)^2=4p(x-h)[/tex] where the focus is [tex](h+p,k)[/tex] and the directrix is [tex]x=h-p[/tex].
Therefore:
[tex]h+p=-6[/tex]
[tex]h-p=-4[/tex]
[tex]2h=-10[/tex]
[tex]h=-5[/tex]
So:
[tex]x=h-p[/tex]
[tex]-4=-5-p[/tex]
[tex]1=-p[/tex]
[tex]-1=p[/tex]
This means that the parabola opens to the left since [tex]p<0[/tex]. Remember that [tex]p[/tex] describes the distance between the vertex and focus point.
We can tell that [tex]k=3[/tex] given the focus point
In conclusion, the equation of the parabola is [tex](y-3)^2=-4(x+5)[/tex]